Hinter der glitzernden Fassade: Über die Macht der Informalität in der Kaukasusrepublik Aserbaidschan - Safiyev, Rail (transcript, 2018)
Daily politics in Azerbaijan: The deceptive contents of a modern autocracy become tangible in this book.